IMPLEMENTASI METODE JIBRIL DALAM PEMBELAJARAN TAHSIN AL-QUR’AN PONDOK PESANTREN PELAJAR DAN MAHASISWA BAITUL QUR’AN AL-FARISY TRENGGALEK - HAFIDZ FAROSY ILMI NUR; Imam Athoir Rokhman (Journal Islamic Studies, 2022)
In the process of learning the qur'an, the method has a very important position in the delivery of goals. This study aims to describe how the implementation of Jibril's method in learning tahsin Al-Qur'an in Baitul Qur'an Al-Farisy Boarding School For Student Trenggalek. Qualitative approach with study case research. The results of the research carried out show that: There are 4 levels of class, namely the beginner class, middle class, advanced class, and muroja'ah class. Supporting and inhibiting factors for the implementation of the Jibril method in learning tahsin Al-Qur'an namely: a. The supporting factors for learning are the presence of professional teachers and the selection of the right method. b. The inhibiting factor for learning tahsin Al-Qur'an is a poor psychological condition so that the learning process can be hampered and the short learning time which causes learning to run less than optimally.